2023
DOI: 10.1186/s13073-023-01160-z
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 splice isoforms generate soluble TREM2 species that disrupt long-term potentiation

Abstract: Background TREM2 is a transmembrane receptor expressed by myeloid cells and acts to regulate their immune response. TREM2 governs the response of microglia to amyloid and tau pathologies in the Alzheimer’s disease (AD) brain. TREM2 is also present in a soluble form (sTREM2), and its CSF levels fluctuate as a function of AD progression. Analysis of stroke and AD mouse models revealed that sTREM2 proteins bind to neurons, which suggests sTREM2 may act in a non-cell autonomous manner to influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…This association was confirmed in our PacBio Iso-Seq targeted dataset with both transcripts associated with genotype (LR.Trem2.62: logFC = 1.73, FDR = 5.2 × 10 −4 ; LR.Trem2.54: log2FC = 1.55, FDR = 3.3 × 10 −6 ) and pathology in TG mice (LR.Trem2.62: logFC = 2.43, FDR = 9.96 × 10 −1 ; LR.Trem2:54: log2FC = 2.20, FDR = 3.85 × 10 −2 ). A significant increase of these two known Trem2 isoforms was also reported in a recent study using qPCR in two transgenic amyloid models of AD 16 ,suggesting that these transcripts are upregulated in response to both tau and amyloid pathology. Notably, the up-regulated mouse LR.Trem2.54 isoform shows high homology with the human TREM2 isoform (ENST00000373113.8, 75.3% homology, 81% query cover) that is most abundantly expressed in the human cortex 17 .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This association was confirmed in our PacBio Iso-Seq targeted dataset with both transcripts associated with genotype (LR.Trem2.62: logFC = 1.73, FDR = 5.2 × 10 −4 ; LR.Trem2.54: log2FC = 1.55, FDR = 3.3 × 10 −6 ) and pathology in TG mice (LR.Trem2.62: logFC = 2.43, FDR = 9.96 × 10 −1 ; LR.Trem2:54: log2FC = 2.20, FDR = 3.85 × 10 −2 ). A significant increase of these two known Trem2 isoforms was also reported in a recent study using qPCR in two transgenic amyloid models of AD 16 ,suggesting that these transcripts are upregulated in response to both tau and amyloid pathology. Notably, the up-regulated mouse LR.Trem2.54 isoform shows high homology with the human TREM2 isoform (ENST00000373113.8, 75.3% homology, 81% query cover) that is most abundantly expressed in the human cortex 17 .…”
Section: Resultssupporting
confidence: 73%
“…We leveraged our full-length Iso-Seq reads to identify a specific differentially expressed transcript (DET) of Gfap (LR.Gfap. 16, Figure 2C) -the most abundantly expressed Gfap isoform (Gfap-201, ENSMUST00000067444.9) in the mouse EC -that was the primary driver of overall differential Gfap expression in TG mice (log2FC = 3.57, FDR = 1.16 x 10 -3 , Figure 2D, Supplementary Table 4). The upregulation of LR.Gfap.16 was confirmed using the hybrid method incorporating normalized RNA-Seq read counts (log2FC = 1.06, P = 2.1 x 10 -2 ), although this approach also identified upregulation of several novel Gfap-associated isoforms (Figure 2E).…”
Section: Whole Transcriptome Long-read Sequencing Identifies Specific...mentioning
confidence: 99%
“… 26 Similarly, a recent research also demonstrated elevated levels of TREM2 alt mRNA and other isoforms in several AD brain regions. 25 One of the few studies addressing the implication of peripheral sTREM2 in AD demonstrated that plasma sTREM2 levels correlate with inflammatory activity in the peripheral circulation and vary across different stages of the disease. 42 Therefore, the findings of the present study suggest that the measurement of TREM2 alt expression in the peripheral blood may reflect the activation of TREM2-related signaling and an altered peripheral immune activity in response to early-stage AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Moutinho and colleagues have presented experimental findings demonstrating that in the human brain, TREM2 alternatively spliced isoforms (TREM2 alt ) are translated and secreted as sTREM2. 25 In accordance with these findings, we compared the peripheral expression of all TREM2 mRNA isoforms and TREM2 alt , which encodes sTREM2, 26 at the same time in patients with mild AD to healthy controls to examine the clinical significance of different mRNA isoforms in this study. MRS was used to investigate the association between peripheral TREM2 expression and central neuroinflammation.…”
Section: Introductionmentioning
confidence: 86%
“…In addition to PBMC-derived macrophages, we have performed experiments using the immortalized human microglial clone 3 cell line, HMC3 (ATCC®CRL-3304). This cell line has been used in multiple studies to investigate intracellular TREM2 biology but not sTREM2 derived from HMC3 cells [ 84 86 ]. Although we were able to successfully knockdown our genes of interest in HMC3 cell line by transient transfection with siRNAs, we were unable to detect any sTREM2 in the conditioned medium even after the medium was concentrated prior to ELISA experiments (Data not show).…”
Section: Methodsmentioning
confidence: 99%